Determining the level of food safety awareness by nutritional literacy in health sciences faculty students - Sevinç, Aliye Yaprak; Demirci, Ülkü (The European Research Journal, 2023)
Objectives: The aim of the research is to determine the nutrition literacy level and food safety awareness level of students who studied at faculty of health sciences. This descriptive study also demonstrates university students’ nutrition literacy statuses, food safety attitudes, nutritional statuses, and food preferences. Methods: The research was conducted as a descriptive and cross-sectional survey study in order to determine the nutrition literacy level and food safety awareness level of the students. Two hundred and eight individuals, including 174 women and 34 men, participated in the study. The data were obtained from face-to-face and online interviews then they were analyzed in a software. The survey is consisted of three parts: socio-demographic form, Evaluation Instrument of Nutrition Literacy on Adults and the Food Safety Attitude scale. Results: In this study, the majority of the participants studied in the department of nutrition and dietetics (55.29%) and audiology (26.92%), followed by health management (7.21%), physiology and rehabilitation (5.77%), nursing (4.33%) and social work (0.48%) department. The relationship between nutrition literacy and food safety among the students of the faculty of health sciences was significant (p < 0.01). Conclusions: This study showed that the nutrition literacy level was sufficient and the food safety attitude was positive in university students. However, it is needed to prospective studies to understand the importance of nutrition literacy and food safety awareness.